A terminalidade humana assistida em ambientes de alta tecnologia médica: a natureza da morte na experiência humana, o diagnóstico médico e a boa morte - Othero, Jairo Constante Bitencourt (Universidade do Vale do Rio dos Sinos, 2016)
This dissertation presents assisted human terminal condition in high-tech medical environments as a new social, medical and technological phenomenon. It discusses the experience of assisting death, the doctor's role, the impact of technology used and the current models for clinical diagnosis of death. The text also suggests care practices for Good Death and examines their moral and cognitive bases, addressing philosophical, scientific and social perspectives on the topic, emphasizing reflective analysis of the phenomena in medical practice. The methodology was a review and a historical-critical analysis of these practices and their philosophical and scientific roots. The dissertation is divided in three chapters, preceded by the introduction and followed by the conclusion. There is also an article attached. In the introduction, a medical interview starts tackling the theme concerning the difficulties of assisted dying. The first chapter shows the sociocultural evolution of the human terminal condition and the role of medical staff and technology in the process. The second chapter describes the experiences of the dying process by those who assist the dying and their impact on the process. The third chapter presents critical analysis of death diagnosis models, contrasting fundamentals with clinical practice. The conclusion discusses medical practices for Good Death, with its pros and cons. The conclusion brings some ideas of each chapter: based on the first chapter, it is concluded that heteronomy ultimately fragment the perception of death. In the second chapter, the conclusion is that death is a triptych process, difficult to understand in an ICU. Finally, the third chapter denies the biological and neocortical models for diagnosis of human death.
Keywords: Morte; Boa morte; Diagnóstico da morte humana; Terminalidade humana; Distanásia; Morte encefálica; Death; Good death; Diagnosis of human death; Terminality; Dysthanasia; Brain death; ACCNPQ::Ciências Humanas::Filosofia